2013 Asilomar Conference on Signals, Systems and Computers 2013
DOI: 10.1109/acssc.2013.6810370
|View full text |Cite
|
Sign up to set email alerts
|

Compressive recovery of 2-D off-grid frequencies

Abstract: Estimation of two-dimensional frequencies arises in many applications such as radar, inverse scattering, and wireless communications. In this paper, we consider retrieving continuousvalued two-dimensional frequencies in a mixture of r complex sinusoids from a random subset of its n regularly-spaced timedomain samples. We formulate an atomic norm minimization program that, with high probability, guarantees perfect recovery from O(r log r log n) samples under a mild frequency separation condition. We propose to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
(46 reference statements)
1
26
0
Order By: Relevance
“…Proof: See Appendix C. Recognizing that (35) is the same as (27), the following proof also establishes Theorem 4. Note that Lemma 2 immediately leads to…”
Section: Lemma 2 Under the Hypothesis (23) One Hasmentioning
confidence: 83%
“…Proof: See Appendix C. Recognizing that (35) is the same as (27), the following proof also establishes Theorem 4. Note that Lemma 2 immediately leads to…”
Section: Lemma 2 Under the Hypothesis (23) One Hasmentioning
confidence: 83%
“…Specifically, consider a time-domain signal of ambient dimension , composed of distinct 2-D complex sinusoids. If the frequencies of the sinusoids lie approximately on the fine DFT grid of the normalized frequency plane [0, 1) [0,1), the signal of interest can be sparsely represented over the DFT basis. It has been demonstrated that the signal can be recovered from a random subset of time-domain samples with a sample size of [14] via basis pursuit [15] or greedy pursuit [16].…”
Section: Introductionmentioning
confidence: 99%
“…This grid-free approach is inspired by the problems of total variation minimization (Candès and Fernandez-Granda 2013) and atomic norm minimization (Tang et al 2013b) to recover super-resolution frequencieslying anywhere in the continuous domain [0,1] -with few random time samples of the spectrally sparse signal, provided the line spectrum maintains a nominal separation. A number of generalizations of off-the-grid compressed sensing for specific signal scenarios have also been attempted, including extension to higher dimensions (Chi and Chen 2013;Chi et al 2011;Xu et al 2014;Yang and Xie 2014).…”
Section: Spectral Estimationmentioning
confidence: 99%